Estudo da variação do perfil químico de Citrus sinensis sobre Citrus limonia após a inoculação da bactéria Xylella fastidiosa - Soares, Márcio Santos (2011)
The present work describes the study of variation in the chemical profile of citrus after inoculation of Xylella fastidiosa, in charge of the Citrus Variegated Chlorosis is one of the most serious diseases that cause damage in Brazilian citrus. The bacterium X. fastidiosa was inoculated in Citrus sinensis grafted on C. limonia and was evaluated using chemometric tools and development of analytical methods such as HPLC-DAD, LC-MS/MS, LC-UV-SPE-NMR and HRMAS quantitative variation of some secondary metabolites such as coumarins and flavonoids identified both in grafts and in the matrix C. sinensis and C. limonia. The chemometric methods PCA and HCA applied to the data obtained in studies by HPLC-DAD and HR-MAS allowed to discriminate plants contaminated with the bacteria of the species healthy, as well as the respective individuals. By analyzing the change in the chemical profile of citrus studied by HPLC-UV-SPE-NMR it was possible to detect the presence of a new class of secondary metabolites derived from p-hidroxy-cinnamic acid containing oxidized dihydropyran and dihydrofuran rings. Similarly, when analyzing the compounds of medium polarity by LC-MS/MS technique was identified, until now, in the roots and leaves several coumarins not cited in the literature for any of the species that constitute the graft, as dihydrosuberenol, 2 ', 3'-dihydrosuberosin, citrubutin the limonoid diosfenol limonin and flavonoid 3-hydroxy-3', 4 ',5,7,8- pentamethoxyflavone. Finally, was observed that coumarin bergapten is present in reasonable quantities only in the leaves of Rangpur lime, which is tolerant to X. fastidiosa, and when the graft presents with symptoms of citrus variegated chlorosis is a small production of this in their leaves, indicating that this is a phytoanticipin.